Legal Protection For Buyers Condotel Affected Pandemics Covid-19 - Suwardi Suwardi; Rossa Ilma Silfiah (Faculty of Law, Pattimura University, 2022)
Providing legal protection for buyers condotel as consumers from developers so legal aspects transition trading should be understood by the buyers as consumers. In the process of the buying and selling of fixed objects such as land, the house, apartment or other property often do we hear terms of agreement? How legal protection for buyers through a binding agreement trading condotel? Methods used in in writing this is normative, referring to act- act which is, law no. 1 year 2020 about flat. In general the contents of a binding agreement trading is the agreement a seller to fastens self will sell them to buyer and accompanied the provision of a sign so or money the based on the agreement. Generally a binding agreement of sale made under the mighty hand for some reason certain as the payment of a price has not been settled. In a binding agreement trading load the deal-agreement about the object promised, the price, when time acquittal and he made certificate trading. For reasons of practicality and a binding agreement trading prepared by the developer or power law (legal officer) a default when binding agreement signed trading, usually a potential buyer given the opportunity to read and studies draft a binding agreement buying and selling beforehand with guided officer readers a binding agreement buying and selling from developers.